Contextual Mathematics Learning Based on Local Wisdom to Improve Understanding of the Concept of Multiplication in Elementary School Students - Matondang, Akhirur Rhomadon (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Mathematics learning at the elementary level often emphasizes abstract symbols and procedural understanding, making it difficult for students to grasp basic concepts such as multiplication. This study aims to improve students’ conceptual understanding of multiplication through contextual mathematics learning based on local wisdom. This descriptive research was conducted at SD Negeri No. 101390 Batang Pane 1, involving 25 third-grade students. The learning process integrated local cultural contexts such as traditional trade and measurement activities. Data were collected through observation, interviews, and tests, and analyzed qualitatively and quantitatively. The findings showed that the students’ average score increased from 58.4 to 84.6, and the learning mastery improved from 44% to 88%. Students were more active and enthusiastic in participating in contextual learning activities that related mathematics to their daily lives. Contextual mathematics learning based on local wisdom effectively enhances students’ conceptual understanding while fostering appreciation for local culture. This approach is recommended for teachers in rural schools to make mathematics more meaningful and culturally relevant.